Validation of cooperative sector study and model contracts for domestic workers in Guyana (2017)
Validates model contracts for the use of individual domestic workers and their employers as well as a contract to be used by the Domestic Workers' Services Cooperative.
Keywords: DOMESTIC WORKERS